Enhancing Mathematical Literacy and Student Engagement through Adventure Pocketbook Integrated with Ethnomathematics-based Problems - Stefany Margaretha Hutauruk; Sekar Lintang Nurshobiha; Vivi Anggraini Saputri Azis (Universitas Syiah Kuala, 2025)
Numeracy literacy is a skill needed. Student engagement in learning affects numeracy literacy. So, it is necessary to implementing adventure pocket book integrated with problem based on ethnomathematics learning. The objectives of this study are (1) to test the effectiveness of the adventure pocket book on student numeracy literacy, (2) to test the effect of student engagement on student numeracy literacy through the implementation of an adventure pocket book, and (3) to describe student numeracy literacy in terms of student engagement through the implementation of adventure pocket book. The research method used is quantitative research. The quantitative approach used is Experimental Design with One-Shot Case Study type. The instruments used were test and questionnaire. The sampling technique is cluster random sampling technique. The subject is class VII. The results showed that the adventure pocket book integrated with problem based on ethnomathematics learning; (1) effectively improved students' numeracy literacy, (2) student engagement can improve numeracy literacy with a large influence of 80% and (3) student engagement in the very high and high categories had an effect on the average completeness of the numeracy literacy test. So, this can be a learning innovation to improve student numeracy literacy and student engagement.